Design and Evaluation of Gastroretentive Ranitidine HCL Sustained Release Bilayer Tablet Using Wax Matrix: A Recent Study - Deshpande, A. H.; Wasule, D. D. (Highlights on Medicine and Medical Research Vol. 6, 2021)
Background: Study of floating bilayer tablets of Ranitidine HCl, H2 receptor antagonist used in the treatment of peptic ulcers is presented. Ranitidine HCl is absorbed only in the initial part of the small intestine and has 50% absolute bioavailability. Materials and Methods: The gas releasing component, necessary for the tablet to float, is added to the food grade rice bran wax matrix layer and the delayed release component, HPMC K100M, formed a separate layer of the bi-layer matrix tablet. The granulated powder blends were evaluated for their properties like Carr’s Index and Hausner’s ratio and compressed into a bilayer tablet. The tablets were evaluated for properties like drug content, buoyancy lag time, buoyancy time, dissolution rate and kinetics of drug dissolution. Results: The gas released made the tablet buoyant. The buoyancy lag time decreased with increase in the rice bran wax amount of the floating component layer. This layer erodes slowly keeping the tablet buoyant for almost 6 hrs. The drug release from the HPMC K100M matrix is delayed for nearly 10 hrs. Conclusion: The concentration of HPMC K100M used in the delayed release component layer can be mucoadhesive. The floating component layer shall keep the tablet buoyant and when it erodes off from the swollen matrix of the delayed release component layer, the swollen matrix being mucoadhesive shall allow the tablet to remain confined to the upper GIT, where the drug has preferential absorption site. This shall improve the bioavailability of the drug.